Ectopic expression of a truncated NLR gene from wild Arachis enhances resistance to Fusarium oxysporum - de Araújo, Amanda Cristina; Brasileiro, Ana Cristina Miranda; Martins, Andressa da Cunha Quintana; Grynberg, Priscila; Togawa, Roberto Coiti; Saraiva, Mario Alfredo de Passos; Miller, Robert Neil Gerard; Guimaraes, Patricia Messenberg (Frontiers in Plant Science, 2024)
Fusarium oxysporum causes devastating vascular wilt diseases in numerous crop species, resulting in substantial yield losses. The Arabidopsis thaliana-F. oxysporum f.sp. conglutinans (FOC) model system enables the identification of meaningful genotype-phenotype correlations and was applied in this study to evaluate the effects of overexpressing an NLR gene (AsTIR19) from Arachis stenosperma against pathogen infection. AsTIR19 overexpression (OE) lines exhibited enhanced resistance to FOC without any discernible phenotype penalties. To elucidate the underlying resistance mechanisms mediated by AsTIR19 overexpression, we conducted whole transcriptome sequencing of an AsTIR19-OE line and non-transgenic wild-type (WT) plants inoculated and non-inoculated with FOC using Illumina HiSeq4000. Comparative analysis revealed 778 differentially expressed genes (DEGs) attributed to transgene overexpression, while fungal inoculation induced 434 DEGs in the OE line, with many falling into defense-related Gene Ontology (GO) categories. GO and KEGG enrichment analysis showed that DEGs were enriched in the phenylpropanoid and flavonoid pathways in the OE plants. This comprehensive transcriptomic analysis underscores how AsTIR19 overexpression reprograms transcriptional networks, modulating the expression of stress-responsive genes across diverse metabolic pathways. These findings provide valuable insights into the molecular mechanisms underlying the role of this NLR gene under stress conditions, highlighting its potential to enhance resistance to Fusarium oxysporum.